PLANT SURFACTANT AS SUSTAINABLE AGENT FOR SILVER NANOPARTICLE SYNTHESIS AND STABILIZATION - Hozana S. Ferreira; Júlio Cesar V. dos Santos; Hugo M. Meira; Renata R. da Silva; Fabíola Carolina G. de Almeida; Leonie A. Sarubbo; Juliana M. de Luna (Química Nova)
This study investigated the use of plant-based surfactants extracted from tangerine peels as nanoparticle stabilizing agents as an environmentally friendly alternative to synthetic surfactants. Three extraction methods were evaluated, with the acid-base method being selected. The plant extract demonstrated emulsifying and surfactant properties, reducing the surface tension of water from 72 to 30 mN m-1 and showing stability under extreme pH and temperature conditions. The extract, which is anionic in nature, was not toxic to aquatic organisms or plant seeds. The surfactant present in the extract was isolated and characterized. The silver nanoparticles stabilized with the biosurfactant were evaluated morphologically and showed stability, rounded shape with sizes between 300-500 nm, with a zeta potential of -86.30 mV and ultraviolet-visible (UV-Vis) microscopy with a maximum peak between 400 and 450 nm, characteristic of silver nanoparticles. These nanoparticles showed antimicrobial activity against Escherichia coli and Staphylococcus aureus. This study suggests the potential of plant biosurfactant as a stabilizer of silver nanoparticles with antimicrobial properties.